2004
DOI: 10.3354/meps273089
|View full text |Cite
|
Sign up to set email alerts
|

Coral-associated Archaea

Abstract: The coral holobiont includes the coral, zooxanthellae, fungi, endolithic algae, and > 30 species of Bacteria. Using culture-independent techniques, we now show that Archaea are also abundant and widespread on corals. Sequence analyses of Archaea on 3 species of Caribbean corals revealed that coral-associated Archaea are novel, diverse, and include representatives from both the Crenarchaeota and Euryarchaeota. Unlike zooxanthellae and Bacteria, the Archaea do not appear to form species-specific associations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
120
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 40 publications
3
120
2
Order By: Relevance
“…Neither pool of origin nor Symbiodinium genotype differentiated overall fungal community structure, and less than half of all OTUs were shared between the pools and Symbiodium genotypes. Similar to patterns described for communities of coral symbiotic bacteria (Rohwer et al, 2001(Rohwer et al, , 2002Sunagawa et al, 2010), archaea (Wegley et al, 2004) and fungal endophyte communities on tropical leaves (Arnold and Lutzoni, 2007), there appears to be overlap of a few select 'core' species among hosts, whereas the majority of 'satellite' species are either transient or endemic to a specific host and locale. Several factors may account for the high level of fungal community dissimilarity found within the pools and the Symbiodinium genotypes.…”
Section: Discussionmentioning
confidence: 54%
“…Neither pool of origin nor Symbiodinium genotype differentiated overall fungal community structure, and less than half of all OTUs were shared between the pools and Symbiodium genotypes. Similar to patterns described for communities of coral symbiotic bacteria (Rohwer et al, 2001(Rohwer et al, , 2002Sunagawa et al, 2010), archaea (Wegley et al, 2004) and fungal endophyte communities on tropical leaves (Arnold and Lutzoni, 2007), there appears to be overlap of a few select 'core' species among hosts, whereas the majority of 'satellite' species are either transient or endemic to a specific host and locale. Several factors may account for the high level of fungal community dissimilarity found within the pools and the Symbiodinium genotypes.…”
Section: Discussionmentioning
confidence: 54%
“…PhyloChip and clone library sequencing as a dual approach to study coral microbiology The availability of universal 16S rRNA gene primers has made it possible to amplify a mixed population of 16S rDNA molecules and to characterize the phylogenetic diversity of coral-associated bacterial communities (Rohwer et al, 2002;Kellogg, 2004;Wegley et al, 2004;Bourne and Munn, 2005). Rohwer et al (2002) estimated a richness of more than 6000 ribotypes in three different coral species based on 1178 sequenced 16S rDNA clones (Rohwer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Reef-building corals are associated with a dynamic, highly diverse consortium of microorganisms that includes protists, bacteria, archaea and endolithic algae and fungi (Shashar and Stambler, 1992;Bentis et al, 2000;Rohwer et al, 2002;Baker, 2003;Kellogg, 2004;Wegley et al, 2004;Rosenberg et al, 2007;Harel et al, 2008). To study the phylogenetic diversity of the bacterial and archaeal components, sequencing the 16S rRNA gene (16S rDNA) is commonly used because of its ability to identify the species without the need for laboratory cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies have described the associated bacteria, especially the bacteria living in the mucus on the surface of corals (Ducklow and Mitchell 1979), and some concluded the specificity of these communities (Rohwer et al 2001;Bourne and Munn 2005). Archae were also reported to live in association with corals (Kellogg 2004;Wegley et al 2004). One study, based on microscopic investigation, reported the discovery of a symbiotic cyanobacteria with in the coral tissue (Lesser et al 2004).…”
Section: Introductionmentioning
confidence: 99%